Prevalence of depression, anxiety, and the related factors in over 50 years adults: Findings from Ardakan cohort study on aging - Ahmad Delbari; Mariye Jenabi Ghods; Mohammad Saatchi; Mohammad Bidkhori; Fatemeh-Sadat Tabatabaei; Mahshid Foroughan; Elham Hooshmand (Golestan University of Medical Sciences, 2024)
Background: Depression and anxiety are the most frequent and devastating mental diseases among older adults. Several variables are identified as contributing to the development of these illnesses. The present study was conducted to investigate the prevalence of depression, anxiety, and their related factors in older individuals residing in Ardakan. Methods: The current cross-sectional study was based on the data obtained from the first phase of the Ardakan aging cohort of 5176 older adults. Depression and anxiety were evaluated using CESD-10 and HADS-A scales, respectively. Moreover, the relationships between these outcomes and the related factors were evaluated using the logistic and linear regression. Results: The prevalence of depression and anxiety was estimated to be about 17% and12%, respectively. Poor perception of health) OR=2.29, CI95% 1.79 to 2.93), Low perceived economic status (OR=2.11, CI95% 1.71 to 2.60), Receiving care (OR=1.66, CI95% 1.39 to 1.97), affecting by neurological disease (OR=1.37, CI95% 1.11 to 1.69), Gastrointestinal diseases (OR=1.48, CI95% 1.23 to 1.77) were significantly associated with the presence of depression. Female gender, Poor perception of health and economic status, receiving, and providing care, and suffering from neurological, cardiovascular, gastrointestinal, and respiratory diseases were related to higher anxiety scores. Conclusion: The prevalence of depression and anxiety among the participants was relatively significant, and these variables were significantly correlated with several factors, including health and economic status and receiving/providing care. These findings highlight the significance of taking into account several socio-economic, health-related, and gender-specific aspects when dealing with mental health disorders including depression and anxiety in this particular age demographic. By identifying the risk factors, healthcare professionals can better target interventions and support systems to manage and mitigate the effect of these mental health disorders.